The sustainable development of a large area. A case study. Kratos 2020 - Verardi, Ferdinando (European Journal of Applied Sciences, 2022)
Applied experience of democratic participation during a multi-agent integrated planning, organized from the bottom up in a territorial mosaic of Vast Area. The debate was feed through the weaker and local actors of governance (understood as "conversation", landscape), feeding awareness, and improve of endogenous processes of sustainable development. The Strategic Plan as a conscious mode to dilate time, and not like a final goal, a spontaneous harmonious link between hierarchies of the territorial attraction centers. A polycentrism of continuity and proximity to the creation of a territorial identity that leans on the environmental and cultural strategy to is determine. A real experience inspired by non-deterministic theoretical scientific approaches (and subordinated to the result); but it based on democratic ideals, while respecting the role of the institutions, ensuring a high value to the cardinal principle of consultation between the government bodies at various levels and encouraging their participation in the territory in a planned and orderly manner in respect of all local actors. The experience is certainly interesting for today's and future operators who will contribute to enhancing the sustainable development of the area, finding utopian guide and inspiration for democratization processes, with the hope that it can become a concrete best practice for developing good democracy and the determination of a coordinated and strategic planning of territories within the European Economic Space.